2016
DOI: 10.2196/mededu.5159
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Augmented Reality in Clinical Simulations: Using Google Glass With Manikins

Abstract: BackgroundStudies show that students who use fidelity-based simulation technology perform better and have higher retention rates than peers who learn in traditional paper-based training. Augmented reality is increasingly being used as a teaching and learning tool in a continual effort to make simulations more realistic for students.ObjectiveThe aim of this project was to assess the feasibility and acceptability of using augmented reality via Google Glass during clinical simulation scenarios for training health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…However, the use of wearable technology can be mostly seen in these two main areas, which are in medical and education. Few studies in medical [27], [32], [33] suggested the inclusion of the use of wearable technology in order to engage the medical students. Wearable technology is a technology that the user can wear on their body.…”
Section: B Wearable Technology In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of wearable technology can be mostly seen in these two main areas, which are in medical and education. Few studies in medical [27], [32], [33] suggested the inclusion of the use of wearable technology in order to engage the medical students. Wearable technology is a technology that the user can wear on their body.…”
Section: B Wearable Technology In Educationmentioning
confidence: 99%
“…Wearable technology is a technology that the user can wear on their body. The recording ability possessed by wearable technology is able to capture a first-person view and realtime video especially for training purpose [27], [32]- [35].…”
Section: B Wearable Technology In Educationmentioning
confidence: 99%
“…However, early attempts at simulating patients in other fields of health sciences using wearable AR glasses can be taken as a demonstration of its feasibility (55). …”
Section: Current State-of-the-art Solutionsmentioning
confidence: 99%
“…One study, conducted at Duke University, developed an educational application of Google Glass to use in conjunction with simulation manikins. 3 As students made different treatment decisions on the manikins, a video would appear in which an actor portrayed how the patient would respond to the treatment.…”
Section: Applications In Medical Educationmentioning
confidence: 99%